Adolescents' Digital activity and its Correlation with Cognitive-Emotional Features, School Performance, and Social and Age Factors: Cross-Sectional Study - George A. Karkashadze; Natalia E. Sergeeva; Leyla S. Namazova-Baranova; Elena A. Vishneva; Elena V. Kaytukova; Kamilla E. Efendieva; Tinatin Yu. Gogberashvili; Dmitriy S. Kratko; Safarbegim Kh. Sadilloeva; Marina A. Kurakina; Anastasiya I. Rykunova; Tatiana A. Konstantinidi; et al. ("Paediatrician" Publishers LLC, 2023)
Background. The study of digital activity correlation with cognitive-emotional features, as well as with other parameters of adolescents' life-activity in non-capital regions of Russian Federation remains relevant.Objective. The aim of the study is to analyze the digital activity structure in adolescents and its correlation with cognitive-emotional features, school performance and social and age factors.Methods. Participants are secondary school students of the 8th-11th grades. Digital activity was examined via online survey among adolescents. We took into account the use of social media, information search, watching videos on the Internet, using of messengers, playing games with electronic devices. Cognitive features (memory, thinking, executive functions, sensory information procession, reading and speech, understanding of emotions, decision-making) and emotional state of adolescents (anxiety) were evaluated by clinical psychologists via various tests. School performance was determined by the recent results of the school quarters/semester finished by the time of the survey. Social and age factors included regular out-of-school physical activity and family structure (complete/ incomplete).Results. We have examined 438 teenagers. 53 (12%) respondents spend more than 5 hours a day with digital devices on weekdays, 133 (30%) - on weekends, 147 (34%) - during the holidays. Structure of digital activity during weekdays (≥ 1 hour) among adolescents was the following: activity in social media prevailed (63.5% of respondents), fewer teenagers searched for information or watched videos on the Internet (47.3 and 42.9%, respectively), about a third (34.9%) played via electronic devices. Structure of digital activity changed over the weekend and during the holidays. We have revealed differences between the information search activity and the volume of short-time memory, understanding the verbal messages, and verbal-logical operations level. Adolescents with different levels of computer gaming activity have shown diversity in sensomotor reaction speed, visuospatial memorization accuracy, number of errors in high-speed reading, reading pace, and understanding text basic meaning.Conclusion. The greater time of digital activity among 8th-11th grades students is associated with negative results of cognitive activity and school performance.